2020
DOI: 10.1002/cne.24898
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of five prosomatostatin genes in the central nervous system of the catshark Scyliorhinus canicula

Abstract: Five prosomatostatin genes (PSST1, PSST2, PSST3, PSST5, and PSST6) have been recently identified in elasmobranchs (Tostivint et al., General and Comparative Endocrinology, 2019, 279, 139–147). In order to gain insight into the contribution of each somatostatin to specific nervous systems circuits and behaviors in this important jawed vertebrate group, we studied the distribution of neurons expressing PSST mRNAs in the central nervous system (CNS) of Scyliorhinus canicula using in situ hybridization. Additional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 118 publications
2
20
0
Order By: Relevance
“…The physiological significance of somatostatin 1 is well established, whereas the different expression patterns of the other somatostatin genes might indicate that the genes have individually differing roles in various species [43]. For instance, sharks and other vertebrates show differential expression of somatostatin genes in different sets of brain neurons [44]. Gene duplication is thought to be a primary source for the evolution of novel functions [45].…”
Section: The Somatostatin Genementioning
confidence: 99%
“…The physiological significance of somatostatin 1 is well established, whereas the different expression patterns of the other somatostatin genes might indicate that the genes have individually differing roles in various species [43]. For instance, sharks and other vertebrates show differential expression of somatostatin genes in different sets of brain neurons [44]. Gene duplication is thought to be a primary source for the evolution of novel functions [45].…”
Section: The Somatostatin Genementioning
confidence: 99%
“…The TSPa/PSPa domain contains ScOtp -expressing cells probably migrated from the TPa/PPa (present results). These cells could give rise to different peptidergic cell types that have been described near the catshark optic chiasm (Met-Enkephalin, Vallarino et al, 1994 ; Tyrotropin Releasing Hormone, Teijido et al, 2002 ; Somatostatin, Sobrido-Cameán et al, 2020 ). Of note, Growth Hormone releasing hormone (Ghrh)-positive cells described in the PSPa of mammals have presumably migrated from the PPa ( Morales-Delgado et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the mammalian ventromedial nucleus seems to be positive for Lhx5 and abuts Dlx -expressing territories at early stages ( Sheng et al, 1997 ; Abellán et al, 2010 ), but it is negative at later stages ( Szabó et al, 2009 ; Heide et al, 2015 ; Miquelajáuregui et al, 2015 ). The catshark NLT presents several types of peptidergic cells (somatostatin, Sobrido-Cameán et al, 2020 ; met-enkephalin and leu-enkephalin, Vallarino et al, 1994 ; melanin-concentrating hormone, Vallarino et al, 1989a ; atrial natriuretic factor, Vallarino et al, 1990b ; delta sleep-inducing peptide, Vallarino et al, 1992 ; beta-endorphin, Vallarino et al, 1989b ; galanin, Vallarino et al, 1991 ; neuropeptide Y, Vallarino et al, 1988 ; corticotropin-releasing factor, Vallarino et al, 1989c ; adrenocorticotropic hormone, Vallarino and Ottonello, 1987 , Vallarino et al, 1989b ), and is thought to be associated with the hypophysis, as reported in actinopterygian fishes (reviewed in Butler and Hodos, 2005 ). The mammalian ventromedial hypothalamus is involved in feeding, fear, thermoregulation, and sexual activity ( Harding and McGinnis, 2005 ; King, 2006 ; Silva et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some samples, ISH for PmCRHBP was followed by immunohistochemistry against PmCRH. These experiments were performed as described in a previous study (Sobrido-Cameán et al, 2020a). Briefly, after the ISH signal was clearly visible, sections were rinsed twice in TBS and treated with 10% H 2 O 2 in TBS for 30 minutes.…”
Section: Double In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%